Accounting problems of foreign nationals - migrant workers - V. A. Lyannoi (Путеводитель предпринимателя, 2020)
The paper presents the analysis of the system of registration of foreign citizens - migrant workers arriving to the territory of the Russian Federation. The main sources of data on migrants, and the problems of ensuring reliability and timeliness ofdata collection arrived.